GAYA KEPEMIMPINAN TRANSFORMASIONAL BERPENGARUH TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR DENGAN DIMEDIASI VARIABEL KEPUASAN KERJA - Wisnawa, I Nyoman Adi; Dewi, A.A Sagung Kartika (E-Jurnal Manajemen; Vol 9 No 2 (2020)DO - 10.24843/EJMUNUD.2020.v09.i02.p07, 2020)
The purpose of this study was to determine the effect of transformational leadership style on Organizational Citizenship Behavior (OCB), to determine the effect of transformational leadership style on job satisfaction, to determine the effect of job satisfaction on Organizational Citizenship Behavior (OCB), and to determine the role of job satisfaction in mediating the influence of job satisfaction transformational leadership style towards Organizational Citizenship Behavior (OCB). This research was conducted at the Office of the Ubung Kaja Village as many as 45 employees using the saturated sample method, collected through a questionnaire using descriptive statistical analysis techniques, path analysis, single test and VAF test. The results showed that the transformational leadership style had a positive and significant effect on Organizational Citizenship Behavior (OCB). Transformational leadership style has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on Organizational Citizenship Behavior (OCB). Job satisfaction positively and significantly mediates the effect of transformational leadership styles on Organizational Citizenship Behavior (OCB). Keywords: Transformational Leadership Style; Job satisfaction; Organizational Citizenship                    Behavior.